THE ECOLOGICAL ESTIMATION OF THE OF ENVIRONMENTAL COMPONENTS BY METHODS OF GEOINFORMATSIYNIH TECHNOLOGIES - Зорін, Д. О. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
The ecological safety of environmental components is estimated by determination of their being in the territory by a selection and analysis of the ground tests, superficial and the ground waters, atmospheric air and vegetation, constructions of databases that ecological-technogeochemical maps with the use of geoinformational technologies and computer technique.